2017
DOI: 10.1017/cjn.2017.210
|View full text |Cite
|
Sign up to set email alerts
|

Combined Stump Pressure and Oximetry for Shunt Use During Carotid Endarterectomy

Abstract: There was poor concordance between TCO and stump pressures, but using both in determining the need for shunt use almost eliminated cross-clamp ischemia in this series of 300 carotid endarterectomy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…The measured value reflects the mix of the arterial and venous oxygen. [4] In patients undergoing CAE under local anesthesia, the cutoff value for stump pressure and NIRS value was determined to avoid neurological deficit. In previous studies, it has been suggested that an intraluminal shunt placement should be performed when the NIRS value after placement of the cross clamp is less than 10% or 20% and stump pressures are lower than 30 or 40 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measured value reflects the mix of the arterial and venous oxygen. [4] In patients undergoing CAE under local anesthesia, the cutoff value for stump pressure and NIRS value was determined to avoid neurological deficit. In previous studies, it has been suggested that an intraluminal shunt placement should be performed when the NIRS value after placement of the cross clamp is less than 10% or 20% and stump pressures are lower than 30 or 40 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been suggested that an intraluminal shunt placement should be performed when the NIRS value after placement of the cross clamp is less than 10% or 20% and stump pressures are lower than 30 or 40 mmHg. [468]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, electroencephalograms (EEGs) and stump pressure have been used to monitor cerebral function and collateral cerebral flow during CEA. 31) Stump pressure <40 mmHg has been used as the threshold for defining cerebral ischemia. 32) Findlay et al 31) demonstrated CEA stump pressure <40 mmHg in 21% of 300 cases.…”
Section: Monitoring Technique In Ceamentioning
confidence: 99%
“…kullanılan bu yöntemin noninvaziv oluşu, diğer yöntemlere kıyasla ucuz ve kolay uygulanabilirliği en önemli avantajlarıdır. Wang ve ark., kross klemp sonrası rSO2'deki %12.3, Jonsson ve ark., %9, Findlay ve ark., >%10 ve Kondov ve ark., >%15 azalmanın yüksek duyarlılık ve kabul edilebilir özgüllük ile güvenli bir eşik değer olduğunu belirtmişlerdir(17,18,19,14). Ancak NIRS'ın pozitif pretiktif değerinin zayıf olması ve serebral iskemi için net bir cut-off değerinin olmaması dezavantajıdır(20).…”
unclassified